The Effect of Earnings Quality on Financial Performance in Indonesia : is the State-Owned Bank better than Private Bank? - Utami, Rachma Bhakti; Nuzula, Nila Firdausi; Damayanti, Cacik Rut (Department of Management, Faculty of Economics and Business, Brawijaya University, 2019)
The primary objective of this study is to analyze the effect of earnings quality on financial performance of banks in Indonesia by comparing the SOEs and private banks. This study uses discretionary accruals and earnings persistence indicators to measure earnings quality, as well as financial performance variables measured through return on assets, return on equity, rate return on loans and total asset turn over. Eight conventional banks compared in this study are 4 government banks and 4 private banks, with research data from 2006-2018. Data is processed using Partial Least Square Multigroup Moderation Technique. The results of this study indicate that earnings quality has a significant effect on financial performance of banks in Indonesia. While the results of bank type moderation show that the effect of earnings quality on financial performance of private banks is greater than that of state-owned banks. This study recommends the importance of applying earnings quality in banks, especially in state-owned banks. Furthermore, this study suggests that government companies should avoid earnings management in order to create good and high quality financial performance, especially in the banking sector in Indonesia.